The international economy - Kenen, Peter B. (Cambridge [England] ; New York, NY, USA : Cambridge University Press, 1994)
This text offers a rigorous introduction to international economics for upper-level undergraduates and above. It examines the causes and effects of international trade and deals with monetary matters. A problem set follows each chapter.
Includes bibliographical references and index.
oif 09/11/15
Loan
Keywords: International economy; International economic relations; International economic; International economic relations - mathematical models